The Effect of Selective and Mass Immunization Against Pneumococcal Infection on the Morbidity and Mortality due to Community-Acquired Pneumonia in Children Under 5 Years of Age - Vadislav V. Semerikov; Elena S. Zubova; Lyudmila V. Sofronova (Union of pediatricians of Russia, 2019)
Background. It is required to perform estimation of epidemiological and cost efficacy (regarding morbidity rate) of mass routine vaccination against pneumococcal infection in Russian children and carried out earlier selective vaccination of children from high-risk groups on the basis of four-year experience. It is also important to estimate the rate of hospital admissions in this patient group, long-term and annual cycles, morbidity age and etiology structure, and mortality due to community-acquired pneumonia as one of the most common form of pneumococcal disease. The aim is to study the effect of selective and mass immunization against pneumococcal infection on the morbidity and mortality due to community-acquired pneumonia in children under 5 years of age. Methods. The analysis of communityacquired pneumonia morbidity (in 2003-2018) and mortality due to pneumonias (in 2003-2018) in children under the 14 years old in Perm was carried out. Serotypes of circulating pneumococcus, etiology of community-acquired pneumonias and immunization cost efficacy (direct expense on health care) were further studied. The analysis of study indexes was carried out following selective (vaccination of at-risk children in 2011-2014) and mass (vaccination of infants in 2015-2018) immunization strategies. Results. The morbidity rate of community-acquired pneumonias decreased by 4.0 times (from 267.0 to 66.7 for 1000) after performing selective vaccination (2011-2014) in at-risk children (frequently and chronically ill children). The morbidity rate of community-acquired pneumonias in non vaccinated children of the same group increased by 2.0 times (from 40.0 to 80.0 for 1000 non-vaccinated). The prophylactic efficacy index was 46.0. Whereby the antibacterial index among vaccinated frequently and chronically ill children was 0.11 on one child. This index has decreased by 2.6 times (from 0.11 to 0.04 on one child) in a year within the framework of prospective controlled randomized clinical study. The antibacterial index among non-vaccinated children of this group remained slightly the same: 0.09 and 0.12 respectively. During the selective vaccination the mortality rate among infants decreased by 2 times: long-term average index was 17.9 (2011-2014) against 35.2 (2003-2010) on 100 thousand children. Mass vaccination of infants against pneumococcal infection has reduced the incidence of community-acquired pneumonias among children under 2 years of age and has led to absence of multiple sites of pneumococcal infection in children's organizations. It also has reduced the number of hospitalized children and achieved zero mortality due to pneumonias in infants by the third year of this immunization strategy implementation. The obtained results were achieved mainly due to circulation of 7 pneumococcal serotypes (6A, 6B, 9V, 14, 19A, 19F, 23F) in children under 5 years of age. The threshold level of vaccination against pneumococcal infection advancing morbidity and mortality due to pneumonias in children was specified. The strategy of mass vaccination of infants was cost-effective. Conclusion. The new data on epidemiological and cost efficacy of various immunization strategies against pneumococcal infection in children was obtained.